STUDI DESKRIPTIF KUALITAS FISIK UDARA DI RUMAH SAKIT X BERDASARKAN PERMENKES NO. 7 TAHUN 2019 - Sandro Wijaya Manullang (2024)
Hospitals are a high risk place for transmission of nosocomial infections through direct contact or airborne transmission. To prevent this, hospitals need to pay attention to the air quality in the hospital. This research aims to determine the air physical quality at Hospital X in accordance with Permenkes No. 7 year 2019. This research was a descriptive quantitative study with the sampling technique used is purposive sampling. A total 43 rooms with 12 different types of them were included as research objects with permission from the hospital management. Temperature, humidity and particulates (PM2.5 and PM10) data were measured directly by using a heat stress meter and a particle counter. The measurement results show that of the 43 rooms, 3 rooms (7%) met temperature quality standards, 41 rooms (95%) met humidity quality standards, none (0%) met PM2.5 quality standards, and all (100%) met PM10 quality standard. As conclusion, that the physical air quality at Hospital X is 50.5%. To improve air quality, the hospital need to monitor and maintain air conditioners and exhaust fans every 3 months, not open room doors for long periods, and insist that cleaning staff clean them evenly.